ANALISIS PENGARUH LABA BERSIH, RETURN ON EQUITY, RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2017-2021 - afriyas, yogi; Vargo Christian L. Tobing, Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2023)
This study aims to determine the analysis of the effect of net income, ROE, ROA on the stock prices ofmanufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX)for the 2017-2021 period. This research consists of variables Net Profit Margin (X1), Return On Equity (X2),Return On Assets (X3) to Stock Price (Y). This study uses quantitative data types, while the data sources usesecondary data with library research data collection techniques. The data processing technique used is dataprocessing with SPSS version 25 software. Based on the results of the study, it was concluded that partiallythe variables of Net Profit Margin (X1), Return On Equity (X2), Return On Assets (X3) showed a significanteffect on stock prices ( Y). The results of the joint test of Net Profit Margin (X1), Return On Equity (X2), ReturnOn Assets (X3) variables show the effect on Stock Price (Y). The coefficient of determination of 58.9%indicates that the variables Net Profit Margin (X1), Return On Equity (X2), Return On Assets (X3) have aninfluence of 58.9% on stock prices and the remaining 41.1% is influenced by variables -other variables thatwere not examined in this study